Comparative Study of Epidural vs. Intravenous Patient-Controlled Analgesia in Abdominal Surgery - Dr. Vinod Govindrao Kinge; Dr. Dhiraj Anil Chaudhari; Dr. Ravindra Dattatray Patil; Dr. Varsha Keshavrao Warke; Dr. Lalit Vasant Patil (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Effective postoperative pain management is crucial for recovery in patients undergoing abdominal surgery. Epidural Patient-Controlled Analgesia (EPCA) and Intravenous Patient-Controlled Analgesia (IVPCA) are prominent methods, but their comparative efficacy and patient satisfaction rates have not been thoroughly explored in this specific surgical context. Objective: This study aims to compare the efficacy, safety, and patient satisfaction of EPCA and IVPCA in managing postoperative pain in patients undergoing abdominal surgery. Methods: A retrospective cohort study was conducted with a sample of 140 patients who underwent various abdominal surgeries and received either EPCA (n=70) or IVPCA (n=70) for pain management. Data on pain scores, patient satisfaction, and complication rates were collected and analyzed. Statistical significance was determined using chi-square tests for categorical data and t-tests for continuous variables. Results: Patients in the EPCA group reported significantly lower pain scores at 6, 12, 24, and 48 hours post-surgery (p < 0.05 for all) compared to the IVPCA group. EPCA was also associated with higher patient satisfaction regarding pain management, ease of use, and overall comfort (p < 0.01). The incidence of nausea and vomiting was significantly lower in the EPCA group (14.3% vs. 35.7%, p < 0.001). There were no significant differences in the rates of respiratory depression and hypotension between the two groups. Conclusion: EPCA provides superior pain control and greater patient satisfaction compared to IVPCA in the context of abdominal surgery, with fewer gastrointestinal side effects. These findings suggest that EPCA should be considered as a preferred method for pain management post-abdominal surgery when clinically appropriate.